Actantial Model Patterns Of Revolutionary Consciousness in Zoulfa Katouh’s As Long As The Lemon Trees Grow - Adilla Tazkya Putri; Zuhrul Anam (Hasanuddin University, 2026)
This study applies Greimas’s (1987) actantial model to analyze how the novel encodes revolutionary consciousness as a structural process. The novel is analyzed using a descriptive qualitative method from the perspective of the protagonist, Salama, based on the axes of desire, transmission, and power across three narrative phases. The research reveals three actantial shifts across the phases: the Sender evolves from an external obligation to a fully self-determined desire, the Receiver expands from self-exclusion to a collective inclusion, and the Opponent evolves from external political forces to a natural obstacle. These shifts correspond structurally to the stages of revolutionary consciousness theorized by Gramsci (1971) and Fanon (1963): subalternity, the phase of struggle, and the phase of agency. The findings reveal that the novel thematizes revolution and structurally defines it; each phase of awareness is expressed as a specific and recognizable actantial configuration. Khawf is the structural connection between the paralysis of Phase 2 and the liberation of Phase 3, and each level of consciousness is represented by a specific actantial configuration. The lemon tree planted in the epilogue marks Salama’s structural emergence as a self-determined subject. This study contributes the first structural-political reading of the novel, addressing a gap in scholarship that has concentrated mostly on romance, psychoanalysis, nationalism, and identity.